2021
DOI: 10.3390/ijerph182010850
|View full text |Cite
|
Sign up to set email alerts
|

Are Public Oral Care Services Evenly Distributed?—Nation-Wide Assessment of the Provision of Oral Care in Japan Using the National Database of Health Insurance Claims

Abstract: The provision of oral health care services is one of the global challenges under the realization of universal health coverage in many countries. Despite the increasing importance of oral health care in an aging society, the disparities in the provision of oral care in Japan have not been clarified. Therefore, this study investigated the status of oral and dental care provision using the National Database of Health Insurance Claims and Specific Health Checkups (NDB) at the level of prefectures and secondary med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The African population shows the lowest prevalence of RFT. The differences in the age of the populations (Jiang et al, 2021 ), the different level of economic development (Bas & Azogui‐Lévy, 2022 ; Listl et al, 2015 ), and the different access to dental health services (Kodama et al, 2021 ) can explain the differences observed between continents. The highest levels of per capita dental expenditures has been found for High‐Income North America, Australasia, Western Europe, High‐Income Asia Pacific, and East Asia (Righolt et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The African population shows the lowest prevalence of RFT. The differences in the age of the populations (Jiang et al, 2021 ), the different level of economic development (Bas & Azogui‐Lévy, 2022 ; Listl et al, 2015 ), and the different access to dental health services (Kodama et al, 2021 ) can explain the differences observed between continents. The highest levels of per capita dental expenditures has been found for High‐Income North America, Australasia, Western Europe, High‐Income Asia Pacific, and East Asia (Righolt et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, to obtain reliable results, the population should be as large as possible [30]. By contrast, as health checkup and medical-expense receipt data have become digitized, dental studies based on big data such as national databases, which are not intended for epidemiological research, are being conducted [31][32][33]. If the reliability of the data can be ensured, self-reported health conditions will expand the range of research.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the highly con dential nature of the information contained in the NDB database, various conditions are imposed on the use of the data, which are not freely accessible to researchers. Contrary, NDB-open data is accessible to everyone free of charge and is actually used for several studies (15)(16)(17).…”
Section: Study Settingmentioning
confidence: 99%
“…An SCR score higher than 100 means the prefecture utlilizes speci c medical/dental care more frequently than the mean of Japan as a whole. For detailed SCR calculations, please refer to previous studies (16,17). The information on treatment for dental caries in children such as llings, prosthetics, and dental pulp extractions was unavailable due to the following two reasons: First, NDB-open data does not provide information on medical/dental claims by prefecture for speci c age groups.…”
Section: Dependent Variablesmentioning
confidence: 99%